2015
DOI: 10.1097/opx.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Optometry Practice and Range of Services in India

Abstract: Most optometrists are engaged in multiple modes of practice, with optical practice, hospital-based practice, and academia being the leading modes. Optometrists need to be more involved in providing the core optometric services of binocular vision and low vision. Higher education has an impact on the level of optometric practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 5 publications
5
29
0
Order By: Relevance
“…14 In-office training imposes time, travel and expense burdens on patients and clinicians, which may lead to low uptake of such training by patients, 15 poor compliance by patients and may affect whether binocular vision services are offered by eye-care practitioners. 16 The Convergence Insufficiency Treatment Trial (CITT) 2 compared four training regimens for the treatment of CI in children. These 12-week treatment regimens were: (i) in-office fusional vergence training plus home-based activities; (ii) home-based computer vergence training; (iii) office-based placebo therapy; and (iv) home-based pencil push-ups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 In-office training imposes time, travel and expense burdens on patients and clinicians, which may lead to low uptake of such training by patients, 15 poor compliance by patients and may affect whether binocular vision services are offered by eye-care practitioners. 16 The Convergence Insufficiency Treatment Trial (CITT) 2 compared four training regimens for the treatment of CI in children. These 12-week treatment regimens were: (i) in-office fusional vergence training plus home-based activities; (ii) home-based computer vergence training; (iii) office-based placebo therapy; and (iv) home-based pencil push-ups.…”
mentioning
confidence: 99%
“…CI may be treated; however, a major barrier to successful coverage is that in‐office treatments have better outcomes than home‐based treatments 2005. In‐office training imposes time, travel and expense burdens on patients and clinicians, which may lead to low uptake of such training by patients,2017 poor compliance by patients and may affect whether binocular vision services are offered by eye‐care practitioners 2015…”
mentioning
confidence: 99%
“…To the best of our knowledge, there are no studies that reported the changes in perception of optometry among the students pursuing the profession. A study by Thite et al 6 reported that the Indian optometrists were involved in a range of services at eye hospitals, optical outlets, and community outreach programs. These findings are similar to our results, however, the retrospective perception of optometry showed conflicting responses which indicate a lack of initial knowledge about optometry practice.…”
Section: Discussionmentioning
confidence: 99%
“…5 They practice in multiple settings such as hospital/clinic-based practice, academics, optical retail, research, administration, marketing, and independent private practice. 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, in actual clinical practice, only 10%-15% of French visually impaired patients are referred to a low vision professional, while it is estimated that 90% of patients could benefit from this support [11]. The underuse of low vision rehabilitation is echoed globally, as for example, in India, only 30% of eligible patients are referred for low vision rehabilitation [24]. Furthermore, practices are not standardized among low vision providers, both in France and world-wide [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%